Manusia dan Tantangan Transhumanisme: Kajian Teologi Konstruktif terhadap Bionic Human dengan Konsep Perikhoresis Kristus - Simanjuntak, Yohana Sri Bintang; Marpaung, Frans Best Soma (Theologia in Loco, 2024)
This article explores the theological conception of humanity within the framework of technological advancement, particularly Transhumanism, through the lens of John of Damascus’s concept of Christ’s perichoresis. The perichoreticconcept demonstrates that Christ, as a single person, embodies two distinct natures—divinity and humanity. In perichoresis, these two natures, while distinct, inhabit one another, allowing for mutual presence and interaction. They give space to each other, encircle one another, and move towards one another in an interpenetrative yet unconfused union, remaining undivided and inseparable. In the Transhumanist era, human existence through robotic enhancements (bionic humans) mirrors the dynamic of perichoresis, representing the coexistence of two distinct elements: the biological and the robotic. These elements inhabit and interact with each other, complementing and permeating one another, without subsuming or eliminating either. Thus, the perichoresis of Christ, as articulated by John of Damascus, serves as a constructive metaphor for understanding human identity in an age of technological integration, which dynamics and becoming.